Sais - Egypt Exploration Society; University of Durham (2001)
[Dt.:] Auf der Website werden Informationen zur Erforschung der altägyptischen Stadt Sais angeboten, vor allem Survey- und Grabungsberichte sowie Photographien.. - [Engl.:] This web site contains information about the exploration of the ancient Egyptian town Sais, especially survey- and excavation reports as well as photographs.